Value-added Processes in Publishing and the Impact of ICTs, the Democratization of Publishing and Globalization. - Ferguson, Stuart (International Journal of the Book, 2007)
The spread of information and communication technologies into publishing is generally seen as a boon - to authors, publishers, readers and a number of intermediaries such as libraries. Like many of the technologies associated with the ‘knowledge society’, publishing technologies are often interpreted as part of a welcome process of democratization, allowing individual authors and organizations to publish reasonably high quality books of their own creation. This paper examines the value-added processes of publishing from the perspective of the Centre for Information Studies, Charles Sturt University - a small, niche librarianship publisher in Australia, with a strong record of book publishing and the beginnings of a presence in e-publishing. Based on the Centre's experience, the paper suggests that the costs of publishing in a growing, competitive and global market make it increasingly difficult for publishers to continue adding value in what many have come to call a knowledge society.